Therapeutic Options for COVID-19: Drug Repurposing of Serine Protease Inhibitor Against TMPRSS2 - Abiyyi, Mohammad Wildan; Dwira, Surya; Bustami, Arleni; Erlina, Linda (UI Scholars Hub, 2023)
The SARS-Coronavirus 2 (SARS-CoV-2) outbreak is a serious global public health threat. Researchers around the world are conducting mass research to control this epidemic, starting from the discovery of vaccines, to new drugs that have specific activities as antivirals. Drug repurposing is a potential method of using drugs with known activity for reuse as COVID-19 therapy. This method has the advantage that it can reduce costs and also the duration in the development of potential drugs. The initial step in drug repurposing can be done computationally to determine the effectiveness and specificity of the drug on the target protein. Molecular docking analysis can see the specific interactions of potential compounds with target proteins by analyzing the energy of the bonds formed. The spike protein of SARS-CoV-2 is a major target in the design and discovery of new drugs for the treatment of Covid-19 disease. In addition, transmembrane protein serine protease (TMPRSS2) from host cells has been shown to have an important role in the proteolytic cleavage of viral spike protein to the ACE2 receptor present in human cells. Based on screening studies, it is known that there are several drugs that have been established that have the potential to inhibit the SARS-CoV-2 transfection mechanism into host cells. 10 potential drug candidates used in this study namely Arbecacin, Bromhexine hydrochloride, Hydroxychloroquine, Camostat mesylate, Darunavir, Dequalinium, Fleroxacin, Lopinavir, Remdesivir, and Octopamine were used in molecular docking. Docking analysis revealed that there were three potential compounds, namely Bromhexine hydrochloride, Camostat mesylate and Octopamine with low binding affinity and inhibition constants. Based on the docking result, Camostat mesylate as the best candidate has a high specific binding affinity for the Ser441 and Asp435 residues present in the TMPRSS2 catalytic triad. Thus, these results reveal the mechanism of inhibition of TMPRSS2 by the known inhibitor Camostat mesylate in detail at the molecular level. Where, Camostat mesylate has a strong bond. This structural information could also be useful for designing and discovering new inhibitors of TMPRSS2, which may be useful for preventing the entry of SARS-CoV 2 into human cells.